HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEMANDIRIAN ACTIVITY OF DAILY LIVING (ADL) PADA PASIEN POST OPERASI - Pratiwi, Rini (Jurnal Keperawatan Profesional, 2023)
Postoperative patients often experience difficulties in carrying out activities of daily living, especially during the recovery period, causing patients to depend on their families and need support in recovery. This study aims to determine the relationship between family support and the level of independence in activities of daily living (ADL) in postoperative patients at Arifin Achmad Hospital Pekanbaru. Method this study used a correlation descriptive design and a cross sectional approach. The research sample was 61 respondents with inclusion criteria using a acccidental sampling technique. The analysis used was univariate and bivariate using the chi-square test. The result of the 61 respondents studied, the majority of postoperative respondents received high family support, totaling 39 respondents, of which 1 (2.6%) were heavily dependent and 38 (97.4%) were independent. The results of the chi-square test in statistical analysis yielded a p value of 0.000 < (α = 0.05) so that H0 was rejected. Conclusion is family support has a relationship with the level of independence in activities of daily living (ADL) in postoperative patients..